Prognostic Factors and Optimal Response Interval for Stereotactic Body Radiotherapy in Patients With Lung Oligometastases or Oligoprogression From Colorectal Cancer - Li, Shuai; Dong, Dezuo; Geng, Jianhao; Zhu, Xianggao; Shi, Chen; Zhang, Yangzi; Wang, Hongzhi; Zhou, Shun; Wu, Hao; Cai, Yong; Li, Yongheng; Wang, Weihu (Frontiers in Oncology, 2019)
Purpose: To analyze the prognostic factors and optimal response interval for stereotactic body radiotherapy (SBRT) in patients with lung oligometastases(OM) or oligoprogression(OP) from colorectal cancer (CRC). Method: Patients with lung OM or OP from CRC treated by SBRT at our hospital were included in this retrospective review. The local control (LC), response to SBRT in different evaluation interval and regional metastases (RM) was analyzed. The risk factor for LC and RM was calculated using the Kaplan-Meier method and compared using the Log-rank test. Multivariate analysis with a Cox proportional hazards model was used to test independent significance.Results: A total of 53 patients with 105 lung metastases lesions treated from 2012 to 2018 were involved in this retrospective review. The median biologically effective dose (BED) for these patients was 100 Gy (range: 75-131.2 Gy). Complete response (CR) increased from 27 (25.7%) to 46 (43.8%) lesions at 1.8 month and 5.3 month following SBRT, and at the last follow-up, 52 (49.5%) lesions achieved CR. The median follow-up duration for all patients was 14 months (range: 5-63 months), and 1-year LC was 90.4%. During the follow-up, 10 lesions suffered local relapse after SBRT (9 of them occurred within 8 months after SBRT). The univariate analysis shows BED≥100 Gy(P = 0.003) and GTV<1.6 cm3(P = 0.011) were better predictors for 1-year LC. The patients with lung oligoprogression had higher 1-year RM when compared with patients with lung oligometastases (hazard ratio 2.78; 95% confidence interval [CI] 1.04–7.48, P = 0.042). Until the last follow up, 4(7.5%) patients suffered grade 2 radiation pneumonitis, and no grade 3-4 toxicity was observed. Conclusions: SBRT provides favorable LC in CRC patients with lung OM or OP, and the GTV and BED can affect the LC. Radiology examinations nearly 5-6 months following SBRT appear to represent the final local effect of SBRT, and the patients with oligoprogression has higher RM.